El futuro de los periódicos on line - Navarro Zamora, Lizy (Estudios sobre el Mensaje Periodístico, 2002)
September 11 2001 was the day when terrorism demonstrated that different models en the Century XXI didn’t function as the people think. These day was when Internet fallen, the deity of the new media. However, the possibilities are latent and we do a question ¿what will be the future of the newspaper on line?, the media that are more in the web, ¿this newspaper has new qualities or is a new version?